" دراسة تأثير جفاف العين على كثافة خلايا بطانة القرنية " - يوسف حبيب; رجب محمود; رجب محمود; صالح رؤى; صالح رؤى (Latakia University Journal -Medical Sciences Series, 2020)
Purpose: To evaluate corneal endothelium cell density (ECD) in patients with dry eye disease (DED)compared to an age-matched control group. Methods: This study included 160 eyes of 80 patients. They were divided into groups based on their dry eye disease severity. All subjects had a complete ophthalmic evaluation including symptoms assessment using the Ocular Surface Disease Index (OSDI), tear break- up time (TBUT) Schirmer1 and then the specular microscope was performed to measure ECD, percentage of hexagonal cells (EX), coefficient of variation CV) and the mean central corneal thickness (CCT).) Results: The mean ECD was significantly lower in subjects with moderate dryness (2714.3 ±138.1 cell/mm²) and severe dryness (2406 ± 129.7 cell/mm²) p=0.001. There were statistically significant correlations between corneal ECD and dry eye severity depending on OSDI score. In addition, the mean (EX) was lower in subjects with moderate dryness (50.07±1.8%) and severe dryness (42.8±3.9%), p=0.001. The mean (CV) was higher in subjects with moderate dryness (42.3±3.9) and severe dryness (47.3±3.5) in, p=0.001. The mean (CCT) was lower in subjects with moderate dryness (568±20.1) and severe dryness (543.1±23.1), p=0.001 Conclusion: There is a significant reduction in corneal ECD in moderate and severe DED which correlates with clinical severity of the disease. الهدف: تقييم كثافة خلايا بطانة القرنية عند مجموعة مرضى جفاف العين ومقارنتها مع مجموعة شواهد متجانسة معها من ناحية العمر. الطرائق: تضمنت هذه الدراسة 160عين ل 80 مريض. تم تقسيم المرضى إلى مجموعات وفق شدة جفاف العين لديهم، خضع كل الأشخاص لفحص عيني كامل متضمناَ مشعر أمراض سطح المقلة، زمن تحطم فيلم الدمع، شيرمر1. ثم خضعوا لفحص بالمجهر المنظاري غير التماسي لدراسة كثافة خلايا بطانة القرنية، نسبة خلايا بطانة القرنية السداسية، معامل التغير في حجم خلايا بطانة القرنية، وثخانة القرنية المركزية. النتائج: أظهرت الدراسة أن متوسط قيم كثافة خلايا بطانة القرنية كان أقل بشكل هام في مجموعة مرضى جفاف العين المتوسط (2714±38,1)خلية/ملم2 والشديد (2406,2±129,7) خلية/ملم2 , 0,001=P. ويزداد انخفاض متوسط قيم كثافة خلايا بطانة القرنية مع زيادة شدة جفاف العين سريرياً وفق مشعر ال OSDI ,بالإضافة إلى انخفاض مهم في متوسط قيم نسبة خلايا البطانة السداسية في مجموعة جفاف العين المتوسط (50,07±1,8)% والشديد(42,8±3,9),0,001=P. وازدياد متوسط قيم معامل تغير حجم خلايا البطانة بشكل هام في مجموعة مرضى جفاف العين المتوسط (42,3 ±1,8) والشديد (47,3±3,5),0,001=P . كما لوحظ انخفاض متوسط قيم ثخانة القرنية المركزية في مرضى جفاف العين المتوسط (568,7±20,1) والشديد (543,1±23,1)،0,001=P الخلاصة: تنخفض كثافة بطانة القرنية بشكل هام في العيون المصابة بجفاف العين المتوسط والشديد ويزداد هذا الانخفاض مع ازدياد شدة الأعراض السريرية لجفاف العين.